Effect of Dapagliflozin on Heart Failure and Mortality in Type 2 Diabetes Mellitus. Issue 22 (28th May 2019) - Kato, Eri T.; Silverman, Michael G.; Mosenzon, Ofri; Zelniker, Thomas A.; Cahn, Avivit; Furtado, Remo H.M.; Kuder, Julia; Murphy, Sabina A.; Bhatt, Deepak L.; Leiter, Lawrence A.; McGuire, Darren K.; Wilding, John P.H.; et al.
Abstract : Background: In DECLARE-TIMI 58 (Dapagliflozin Effect on Cardiovascular Events–Thrombolysis in Myocardial Infarction 58), the sodium-glucose cotransporter 2 inhibitor dapagliflozin reduced the composite end point of cardiovascular death/hospitalization for heart failure (HHF) in a broad population of patients with type 2 diabetes mellitus. However, the impact of baseline left ventricular ejection fraction (EF) on the clinical benefit of sodium-glucose cotransporter 2 inhibition is unknown. Methods: In the DECLARE-TIMI 58 trial, baseline heart failure (HF) status was collected from all patients, and EF was collected when available. HF with reduced EF (HFrEF) was defined as EF <45%. Outcomes of interest were the composite of cardiovascular death/HHF, its components, and all-cause mortality. Results: Of 17 160 patients, 671 (3.9%) had HFrEF, 1316 (7.7%) had HF without known reduced EF, and 15 173 (88.4%) had no history of HF at baseline. Dapagliflozin reduced cardiovascular death/HHF more in patients with HFrEF (hazard ratio [HR], 0.62 [95% CI, 0.45–0.86]) than in those without HFrEF (HR, 0.88 [95% CI, 0.76–1.02]; P for interaction=0.046), in whom the treatment effect of dapagliflozin was similar in those with HF without known reduced EF (HR, 0.88 [95% CI, 0.66–1.17]) and those without HF (HR, 0.88 [95% CI, 0.74–1.03]). Whereas dapagliflozin reduced HHF both in those with (HR, 0.64 [95% CI, 0.43–0.95]) and in those without HFrEF (HR, 0.76 [95% CI, 0.62–0.92]), it reduced cardiovascular death only in patients with HFrEF (HR, 0.55 [95% CI, 0.34–0.90]) but not in those without HFrEF (HR, 1.08 [95% CI, 0.89–1.31]; P for interaction=0.012). Likewise, dapagliflozin reduced all-cause mortality in patients with HFrEF (HR, 0.59 [95% CI, 0.40–0.88;) but not in those without HFrEF (HR, 0.97 [95% CI, 0.86–1.10]; P for interaction=0.016). Conclusions: In the first sodium-glucose cotransporter 2 inhibitor cardiovascular outcome trial to evaluate patients with type 2 diabetes mellitus stratified by EF, we found that dapagliflozin reduced HHF in patients with and without HFrEF and reduced cardiovascular death and all-cause mortality in patients with HFrEF. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT01730534. Abstract : Supplemental Digital Content is available in the text.